What is the link between religión and violence? an assement of the literature (2010)
This article critically reviews the main debates and literature produced by international relations and comparative politics scholars connecting religion to the eruption of violence. Centrally, it argues that, despite fierce fractionalization in other fields of study, academic work on the religion-violence nexus seems to be reaching an emerging consensus between rationalist and constructivist approaches, approximating what Katzenstein and Sil have recently dubbed "eclectic theorizing." It also surveys the virtues and weaknesses of current work, and suggests avenues for future research.